The development of a self-efficacy scale for scientific research and an evaluation of prospective teachers' views about that scale - Tuncer, Murat; Ozeren, Ender (Elsevier Science Bv, 2012)
As with any profession, information changing because of developing technology or making the spreading of information easier exposes teachers to the need for new skills. On the one hand, teachers transfer the knowledge they gained during their school education to their students; on the other hand, they have to follow new information, question this information scientifically, and configure it according to a scientific methodology. Success in this process is closely related to whether the teachers come from a scientific research culture. This research is planned on the basis of the state of this problem. Within this research, firstly a scale has been developed to assess prospective teachers' scientific research self-efficacy. Through the implementation of this scale, prospective teachers' self-sufficiency in scientific research has been compared in terms of gender, department and the idea of academic career. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Ayse Cakir Ilhan
World Conference on Design, Arts and Education (DAE) -- MAY 01-04, 2012 -- Antalya, TURKEY
Keywords: Teacher Training; scientific research self-efficacy; views of prospective teachers; developing scale